AKSIOLOGI KEMAMPUAN BERPIKIR KRITIS - Armansyah Armansyah; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Jurnal Cakrawala Ilmiah, 2022)
In the 21st century In the current development of technology and information, students must have basic skills. Critical thinking skills are one of these basic abilities. This article examines the axiology of reasoning ability and how education can benefit from it. This will allow educators to realize their ability to produce students who are skilled in line with their training objectives in the future. The consequences of writing concentrating on decisive reasoning abilities are found in axiological reviews, especially the reasoning abilities that are determined to be arranged consistently. will be a trend, so that when students are in a problem, they can make choices quickly, appropriate, and productive. Students will be able to compete in the globalization era thanks to these critical thinking skills.